China's future : the path to prosperity and peace - Canrong, Jin (Enrich series on insights into China., 2014)
"Since the policy of reform and opening up was started in December 1978, China has undergone a marked economic and social transformation. Analyzing the current conditions of the country, China's Future: The Path to Prosperity and Peace offers a vivid account of China's macro successes together with the challenges and setbacks the nation faces, as well as the path towards a bright future"--Page 4 of cover.